2020
DOI: 10.1002/adma.201907995
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Pore Structures of MOFs for Record High Hydrogen Volumetric Working Capacity

Abstract: Metal–organic frameworks (MOFs) are promising materials for onboard hydrogen storage thanks to the tunable pore size, pore volume, and pore geometry. In consideration of pore structures, the correlation between the pore volume and hydrogen storage capacity is examined and two empirical equations are rationalized to predict the hydrogen storage capacity of MOFs with different pore geometries. The total hydrogen adsorption under 100 bar and 77 K is predicted as ntot= 0.085× Vp − 0.013× Vp2 for cage‐type MOFs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(118 citation statements)
references
References 53 publications
2
115
0
1
Order By: Relevance
“…The DOE targets are 4.5 wt% (gravimetric working capacity) and 30 g L −1 (volumetric working capacity) by 2020. Some MOFs satisfy the DOE gravimetric target so far [60] .…”
Section: Mof Commercialization Criteriamentioning
confidence: 99%
“…The DOE targets are 4.5 wt% (gravimetric working capacity) and 30 g L −1 (volumetric working capacity) by 2020. Some MOFs satisfy the DOE gravimetric target so far [60] .…”
Section: Mof Commercialization Criteriamentioning
confidence: 99%
“…45 To increase adsorbed hydrogen density, efforts have focused on optimizing pore dimensions and total pore volume of porous materials, aided by computational efforts that can screen databases of model MOF structures. [46][47][48] Research has also been carried out on more efficient packing of adsorbent materials within the storage vessel to minimize free space. These efforts have included engineering crystal geometrics, investigating compaction methods, and developing nearcrystal-density monoliths.…”
Section: Adsorbentsmentioning
confidence: 99%
“…However, high compression pressure of MOFs resulted in pellet with narrow pore apertures which yielded low volumetric and gravimetric H 2 useable capacities. 141,142 Recently, Chen et al 143 reported BET surface area of 7310 m 2 g −1 and volumetric BET surface area of 2060 m 2 cm −3 for NU-1501-Al. High gravimetric and volumetric storage capacities of 14.0 wt% and 46.2 g/L respectively were obtained under temperature and pressure swing of 77K/100 bar to 160K/5 bar.…”
Section: Mechanism Of Hydrogen Adsorption Of Mofsmentioning
confidence: 99%